Comparison of sensitivity of lung ultrasound and chest x-ray imaging for the diagnosis of community-acquired pneumonia in children: Primerjava občutljivosti ultrazvoka in rentgenskega slikanja pljuč za diagnosticiranje zunajbolnišnične pljučnice pri otrocih - Berce, Vojko (Acta Medico-Biotechnica, 2021)
Purpose: Lung ultrasound (LUS) has only recently been considered to be a suitable tool for diagnosing community acquired pneumonia (CAP) in children. Little is known about the usefulness of LUS in different types of pneumonia. Therefore, we analyzed and compared the sensitivity of chest X-ray (CXR) and LUS in different etiological types of CAP in children. Methods: We performed a prospective study in 166 children with CAP, who were admitted to the hospital. The participants were stratified into bacterial (n=80), atypical bacterial (n=32) and viral (n=54) pneumonia subgroups, according to the laboratory and microbiological results. LUS and CXR were performed on all patients at admission. Results: Pneumonia was detected with LUS in 161 (97.0%) participants and with CXR in 137 (82.5%) participants (p<0.01). The sensitivity of LUS was calculated as 97.0% (95% CI, 93.1%–99.0%), and the sensitivity of CXR as 82.5% (95% CI, 75.9%– 88.0%), p<0.01. In patients with bacterial CAP, infiltrates were detected with LUS in 79 (98.7%) and with CXR in 67 (83.8%) of cases (p<0.01); in atypical bacterial CAP, with LUS in 30 (93.8%) and with CXR in 28 (87.5%) (p=0.69); and in patients with viral CAP with LUS in 52 (96.3%) and with CXR in 42 (77.8%) (p<0.01). Conclusion: We have determined that LUS is an excellent tool for diagnosing CAP in children. LUS is at least as sensitive as CXR in all types of CAP in children and will probably replace it as the investigation of choice in CAP.